Implications of feed and seed costs in Asian seabass mariculture in the face of climate change - Divu, Damodaran Nair; Mojjada, Suresh Kumar; Sudhakaran, Prateesh Omana; Sundaram, Swathi Lekshmi Perumal; Menon, Muktha; George, Grinson; Tade, Mayur Shivdas; Mojjada, Ramesh Kumar; Radhakrishnan, Kalidoss; Vishwambharan, Vinuja Syamala; Shree, Jai; Subramanian, Aarsha; et al. (Frontiers in Sustainable Food Systems, 2024)
Mariculture, a sustainable and rapidly growing aquaculture sub-sector, meets global seafood demand while reducing strain on wild fish stocks and continues to expand worldwide. However, rising feed and seed costs pose significant challenges, overshadowing other farming expenses. Climate change exacerbates the profitability of sea cage farming, increasing volatility. The surge in fishmeal costs has a detrimental impact on operational expenditure (Opex) and continues to be a threat. Consequently, sea cage farming in India is at a critical juncture, needing a balance between technological advancements and stakeholders' fiscal needs. In this context, this study examines peer-reviewed synthesized data by employing metrics, to evaluate the implications of feed and seed costs in Asian Seabass (Lates calcarifer) sea cage farming over 10-year horizon being assessed. The total sales revenue over the 10-year period was USD 100,848, with a net profit of USD 55,198.89. A 30% increase in feed and seed prices significantly altered the economic dynamics of the enterprise, leading to an 8.8% and 9.2% rise in the respective break-even points. There was also a significant effect on the BCR, with a 30% increase in each factor resulting in a 10% and 18% change in the projected BCR, respectively. Therefore, the significance of feed and seed cost has been established, and necessitating an inevitable shift from low value fish to formulated feed adaption for sustainable mariculture development. The study suggests improvements to existing practices to maximize efficiency and minimize production costs.